Function and clinical relevance of RHAMM isoforms in pancreatic tumor progression - Choi, Soyoung (Mol Cancer, 2019)
The receptor for hyaluronic acid-mediated motility (RHAMM) is upregulated in various cancers. We previously screened genes upregulated in human hepatocellular carcinomas for their metastatic function in a mouse model of pancreatic neuroendocrine tumor (PNET) and identified that human RHAMM(B) promoted liver metastasis. It was unknown whether RHAMM(B) is upregulated in pancreatic cancer or contributes to its progression. In this study, we found that RHAMM protein was frequently upregulated in human PNETs. We investigated alternative splicing isoforms, RHAMM(A) and RHAMM(B), by RNA-Seq analysis of primary PNETs and liver metastases. RHAMM(B), but not RHAMM(A), was significantly upregulated in liver metastases. RHAMM(B) was crucial for in vivo metastatic capacity of mouse and human PNETs. RHAMM(A), carrying an extra 15-amino acid-stretch, did not promote metastasis in spontaneous and experimental metastasis mouse models. Moreover, RHAMM(B) was substantially higher than RHAMM(A) in pancreatic ductal adenocarcinoma (PDAC). RHAMM(B), but not RHAMM(A), correlated with both higher EGFR expression and poorer survival of PDAC patients. Knockdown of EGFR abolished RHAMM(B)-driven PNET metastasis. Altogether, our findings suggest a clinically relevant function of RHAMM(B), but not RHAMM(A), in promoting PNET metastasis in part through EGFR signaling. RHAMM(B) can thus serve as a prognostic factor for pancreatic cancer. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12943-019-1018-y) contains supplementary material, which is available to authorized users.